Use of Non-conventional investigation techniques in a case of foreign body impaction in oesophagus- our experience - Walvekar L1 , Praveen Kumar P2 , Rajkumar2 , Kasturi RR3 (Perspectives In Medical Research, 2019)
Chronic alcoholism impairs the lung’s defensive mechanism leading to an increased susceptibility to respiratory infections, in turn, leading to increased incidence of ARDS in these populations . Alcoholics are also at risk of developing aspiration which is common in an intoxicated person due to the loss of protective airway reflex after he/she “passes out”. The usual thought process that runs in mind when a foreign body oesophagus presents is to perform a CT scan to know the position of the foreign body and then proceed with further management techniques.